2007
DOI: 10.1167/iovs.06-1085
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Laser-Induced Choroidal Neovascularization by Atorvastatin by Downregulation of Monocyte Chemotactic Protein-1 Synthesis in Mice

Abstract: Atorvastatin effectively inhibited laser-induced CNV in mice and was associated with downregulation of CCL2/MCP-1 and VEGF and reduced macrophage infiltration into the RPE/choroid.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
56
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 61 publications
(61 citation statements)
references
References 28 publications
5
56
0
Order By: Relevance
“…This implies better choroidal flow and consequently oxygenation of the external retina, reducing chronic ischaemia [157]. It is well known that statins can exert cholesterol-independent or pleitropic effects [11] which involve the restoration of endothelial function, stabilization of atheromatous plaque, reduced oxidative stress, or lower eye inflammation [150,153,178]. These effects are potentially decisive in maintaining normal endothelial and smooth-muscle function and in improving endothelium-dependent relaxation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This implies better choroidal flow and consequently oxygenation of the external retina, reducing chronic ischaemia [157]. It is well known that statins can exert cholesterol-independent or pleitropic effects [11] which involve the restoration of endothelial function, stabilization of atheromatous plaque, reduced oxidative stress, or lower eye inflammation [150,153,178]. These effects are potentially decisive in maintaining normal endothelial and smooth-muscle function and in improving endothelium-dependent relaxation.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, statins could be beneficial not only for their lipid-lowering properties but for their other effects referred to as pleiotropic -that is, their capacity to restore endothelial function, to stabilize atherosclerotic plaque, or to alleviate oxidative stress and vascular inflammation [150][151][152][153]. Such effects have been demonstrated in rabbits fed cholesterol at a dose insufficient to reduce plasma-cholesterol levels [55,148].…”
Section: Statinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, Yamada et al [71] showed that treatment of mice with atorvastatin decreases Ccl2 levels, thereby reducing ocular infiltration of macrophages and decreasing laser-induced CNV volume. Both of these studies showing decreased laser-induced CNV in the absence of Ccr2 or Ccr2 are in stark contrast with the previously described study by Ambati et al in which deficiencies of these chemokines led to AMD features, including CNV, in senescent mice [63,70,71]. Indeed, these contradictory findings in Ccr2-or Ccl2-deficient mice with laserinduced CNV versus CNV associated with senescence highlights the potentially dissimilar mechanisms underlying laser-induced CNV and CNV associated with age-related maculopathy.…”
Section: Manipulating Macrophages In Animal Models Of Cnvmentioning
confidence: 91%
“…Moreover, macrophages isolated from eyes after laser injury express angiogenic factors and exhibit angiogenic activity in vitro [70]. Similarly, Yamada et al [71] showed that treatment of mice with atorvastatin decreases Ccl2 levels, thereby reducing ocular infiltration of macrophages and decreasing laser-induced CNV volume. Both of these studies showing decreased laser-induced CNV in the absence of Ccr2 or Ccr2 are in stark contrast with the previously described study by Ambati et al in which deficiencies of these chemokines led to AMD features, including CNV, in senescent mice [63,70,71].…”
Section: Manipulating Macrophages In Animal Models Of Cnvmentioning
confidence: 97%